High-Sensitivitycardiac Troponinsin Cardio-Healthy Subjects: A Cardiovascular Magnetic Resonance Imaging Study. Issue 1 (December 2018) - Aw, Tar-Choon; Huang, Wei-ting; Le, Thu-Thao; Pua, Chee-Jian; Ang, Briana; Phua, Soon-Kieng; Yeo, Khung-Keong; Cook, Stuart; Chin, Calvin
Abstract The 99th percentile upper reference limits (URL) of high-sensitivity cardiac troponin (hs-cTn) in healthy subjects are essential for diagnosis and management of cardiovascular diseases. Unless screened stringently, subclinical disease affects the derived URL. In 779 healthy subjects(49% males; 17–88 years) screened by cardiovascular magnetic resonance (CMR), the gold standard for assessing cardiac volumes and myocardial mass; and estimated glomerular filtration rate (eGFR), the 99th percentile URL of hsTnT (Roche) and hs-cTnI (Abbott) were similar to the published URL. The overall 99th percentile URL of hsTnT and hsTnI were 15.2 and 21.2 ng/L, respectively; males had higher values than females (hsTnT: 16.8 versus 11.9 ng/L and hsTnI: 38.8 versus 14.4 ng/L). Correlation between hsTnT and hsTnI was modest (r = 0.45; p < 0.001). A larger proportion of healthy volunteers <60 years had detectable hsTnI compared to hsTnT (n = 534; 30.0% versus 18.3%, p < 0.001). Lower eGFR was an independent clinical determinant of hsTnT, but not hsTnI. Both hs-cTn concentrations were independently associated with myocardial mass and cardiac volumes (p < 0.01 for all), but only hsTnI was independently associated with CMR multi-directional strain measures and extent of LV trabeculations (p < 0.05 for all). Differences exist between hs-cTn assays and may influence their selection depending on cardiac conditions, patient population and local factors.